Flash glucose monitoring in type 1 diabetes: A comparison with self‐monitoring blood glucose - Babaya, Naru (J Diabetes Investig, 2020)
AIMS/INTRODUCTION: A flash glucose monitoring (FGM) system has become available. To clarify the relationship between FGM and self‐monitoring blood glucose (SMBG) values, we compared the two values after simultaneous measurement in Japanese patients with type 1 diabetes, under daily life settings. MATERIALS AND METHODS: A total of 20 outpatients with type 1 diabetes were analyzed. When FGM and SMBG were carried out simultaneously (within ±3 min), the values were adopted and each FGM value was matched and compared with the corresponding SMBG value. In addition, we analyzed other cases of simultaneity defined as “within ±2 min,” “within ±1 min” and “at the exact same time.” RESULTS: The percentage of SMBG and FGM values in the clinically acceptable zone A + B in Clarke and consensus error grid analyses were 97.9 and 99.2%, respectively. Deming regression (x‐axis: FGM values, y‐axis: SMBG values) determined a slope of 0.9128 (95% confidence interval 0.9008–0.9247) and an intercept of +15.94 mg/dL (95% confidence interval 14.05–17.84). FGM values were lower than SMBG values in the lower glucose range, and higher in the higher glucose range. The shorter the time lag between measurements, the higher the rate of concordance between FGM and SMBG values. CONCLUSIONS: The results of this study provided evidence on the reliability of FGM in Japanese patients with type 1 diabetes in home conditions. Based on the results, if an abnormal glucose value is detected by FGM, SBMG should then be used to confirm the result.